A Critical study of the Notion of Shiite Hadith Scholars’ Turning Away from Isnad (documentation - Mohammad Kazem Rahman Setayesh; mahdi qolamali (تحقیقات علوم قرآن و حدیث, 2015)
Observing documentation of hadith (isnad), has witnessed ups and downs at different eras ,among Shia and Sunni scholars. Over the past centuries some Sunni scholars such as Ibn Taymiyyah and Suyuti have accused Shia of neglecting isnad , and therefore condemning them for it. Contemporary Sunni scholars have further claimed that observing documentation (isnad) is specific to Sunnis from which the Shia have copied since the fourth century on. This article has rejected  these accusations based on  the following arguments , citing examples for each : 1) Ahl-ol-Bayt’s emphasis on documentation and the  narrators’ qualities, 2) Ahl-ol-Bayt’s observance of documentation 3) compilation of documented (musnad) hadith and rijal works before the fourth century, 4) Shiite  hadith scholars’ practical efforts in documentation, 5) and Shiite scholars’ views on documentation. These evidences shows  that the origin of such an accusation is ignorance  and bias  on part of the opponents